A Improving The First Year Students’ Vocabulary Skill Using Song at SDN Mojoagung 3, Prambon, Nganjuk in the Academic Year 2021/2022 - Yusniarsi Primasari; Winarsih (Universitas Islam Balitar, 2022)
Vocabulary is one of the important components of language that must be taught to the students of Elementary School. It is usually taught in relation to four other language skills (listening, speaking, reading, and writing). The vocabulary teaching using song is very effective because children like to sing a song. Based on the preliminary study, the students who passed the test were 57% and 43% were unsuccessful. It indicated that the student's achievement was low because they did not know the English name for anything about “Happy Birthday”. This problem makes the students lack motivation in learning English. Therefore, this study aimed to improve the students’ vocabulary skills using songs. The design of this research is a Classroom Action Research. There are two cycles in this research, namely Cycle I and Cycle II. Each cycle consists of four steps: planning, acting (implementing), observing, and reflection. This research took two cycles because it's impossible to improve students’ vocabulary mastery it only took one cycle and also useful to compare the result of the test. The criteria of success of this research if there were that 75% of students scored 60 or higher. The result of the study showed that the number of students in the passing grade (60) has increased. The students who got 60 and more were 57% in the preliminary study. After being taught by song, the students who got 60 and more increased to 71%, and in cycle II increased to 85%. The improvement could be gained when the student's performance during the learning-teaching process was satisfied. The classroom situation was enjoyable and the students were active during the learning-teaching process. The materials given were suitable for the lessons, attractive, or caught the students’ attention and contextual. Based on the research analysis as explained above, the researcher concludes that teaching vocabulary through song effectively improves the students’ vocabulary mastery.